DESAIN SPWM SINGLE PHASE FULL BRIDGE INVERTER PADA SISTEM UNINTERRUPTIBLE POWER SUPPLY 500W - Indra Ferdiansyah; Indhana Sudiharto; Epyk Sunarno; Mahbub Gusti Muhammad (Jurnal Arus Elektro Indonesia, 2021)
Indonesia has sufficient power resources provided by PLN. However, blackouts still occur frequently due to several reasons, such as disruption in transmission and distribution, especially when the weather is raining. This has an impact on customer inconvenience. To overcome this, several houses have used a backup power source in the form of a generator set that will be operated by a blackout. This solution turns out to cause noise that can interfere with user comfort. To increase user convenience, a system (Uninterruptible Power Supply) is proposed. The system there is a voltage sensor to detect a power outage. In addition, there is an SSR switch so that it can to switch main source to the UPS with a fast response time during a blackout. The inverter on UPS system uses the SPWM technique to produce a sine wave output, then the use of an LC filter to reduce ripple on the system. PID-based voltage control is used to maintain the output inverter by the setting value of magnitude amplitude. Based on the results of the test, the UPS can work during a blackout with a maximum power of 500W and the voltage constant at 215V. Keywords — Blackout, PI Controller , SPWM, UPS.